Criptomonedas y Blockchain en el ámbito financiero: Un análisis de correlación; Cryptocurrencies and Blockchain in the financial field - David Patricio Lozano (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– In this article, we carry out a study about one of the most disruptive topics in recent times: cryptocurrencies. Whether as a revolution in payment methods, because it is a speculative asset or because of the particularities of the technology on which it is supported, cryptocurrencies are generating a greater impact on our lives, especially in the world of finance. The main objective that we set ourselves is to delve into the knowledge of cryptocurrencies and the technology that supports them, in a way that allows us to have a clear idea of the consequences that their appearance has not only in the financial field, but also in the economy in general. If we make an approximation to these cryptocurrencies and blockchain technology, we will be able to be aware of the advantages of their use, as well as the disadvantages of their existence, which will allow us to be aware of the role that this technology can play in the present, in the short term and long term, especially in the business field. After this analysis of the origins of Bitcoin and its evolution, we study its correlation with several assets and indices: Ethereum (second cryptocurrency with the highest value), gold (commodity considered as a refuge value), S&P500 (the most representative index of the US market) and the MSCI World Index (most representative global index), briefly explaining each of these assets, to finally analyze their correlation with Bitcoin from the year for which we have data for each one.
Keywords: M15; O16; G10; 330; cryptocurrencies; blockchain; bitcoin